APPLICATION OF THE STUDENT TEAM ACHIEVEMENT DIVISION (STAD) COOPERATIVE LEARNING MODEL TO IMPROVE LEARNING ACTIVITIES AND ACHIEVEMENTS AND STUDENTS OF CLASS X SMANEGERI 1 MERAPI SELATAN (Classroom Action Studies in Biology Class X Subject) - Sri Widiarti; Bambang Sahono (DIADIK, 2019)
The research perpuse is to describe the learning method Student  Team Achievement Division to increase  the activity and achievement of the student learning.This research using  classroom action research and quotient experiment. The subject in this research is the student of IPA class X at the first  semester  in academic year 209/2020 of SMA Negeri 1 Merapi Selatan. The experimenting quotients are X IPA1 class and X IPA3, class. The collecting data in this research is using the students’ ability observation sheet. The analysis of the data is using the descriptive statistic that  is mean.  From the  result of this research  shows that the learning method Student  Team Achievement Division  can in crease activity and achievement of the students learning of X IPA class in  SMA Negeri 1 Merapi Selatan